Comparativo de custos dos sistemas construtivos wood frame e concreto armado para edifício utilizando BIM 5D - Leandro Dias Viana (2020)
This dissertation deals with the comparison of the construction costs of the wood frame and conventional structures in reinforced concrete and masonry using BIM 5D. The wood frame system consists of the development of structural walls with wooden uprights, usually of pine, with closing and locking and oriented strip of wood strips (Oriented Strand Board - OSB). The main objective of this work is to analyze the economic viability of using the wood frame construction system for the construction of buildings in Brazil in detriment to the conventional construction method in reinforced concrete and masonry. Building Information Modeling (BIM) is developed for the design of a three-story building in both construction systems and their budget is elaborated using the BIM 5D methodology to perform the cost comparison. As a result, a comparative analysis is presented on the economic viability of using this constructive alternative in the country in relation to the conventional constructive system, thus providing a scientific basis for its greater implementation. Results of the benefits achieved by using BIM to extract quantities for budgeting with Revit software and construction simulation with Navisworks and technical aspects for its use and a procedure of the combination of BIM modeling and budgeting for wood frame building are also presented.